Sistema supervisório para poços de petróleo baseados no método de elevação artificial Plunger Lift - Soares, Lennedy Campos (2010)
The several existing methods for oil artificial lifting and the variety of automation equipment for these methods many times lead the supervisory systems to be dedicated to a unique method and/or to a unique manufacturer. To avoid this problem, it has been developed the supervisory system named SISAL, conceived to supervise wells with different lifting methods and different automation equipments. The SISAL system is working in several Brazilian states but, nowadays, it is only supervising rod pump-based wells. The objective of this work is the development of a supervision module to the plunger lift artificial lift method. The module will have the same characteristics of working with automation hardware of many manufacturers. The module will be integrated to the SISAL system, incorporating the capacity to supervise the plunger lift artificial lift method.